Geological and seismological evidence for NW-SE crustal extension at the southern margin of Heraklion basin, Crete. - Ganas, Athanassios; Fassoulas, Charalambos; Moshou, Alexandra; Bozionelos, George; Papathanassiou, George; Tsimi, Christina; Valkaniotis, Sotirios (Bulletin of the Geological Society of Greece, 2017)
In this paper we present new geological and seismological data on the orientation of crustal extension in central Crete (SE Heraklion basin) following the occurrence of two shallow seismic sequences: a) the May 2005 Assimi M=4.1 earthquake sequence and b) the 2013 Houdetsi-Tefeli sequence (3.2≤Mw≤3.6). Emphasis is given to the results of the geological field work, stress analysis, source inversion, aftershock relocations and mapping of earthquake-induced environmental effects. For the first time we find seismological evidence for N-S strike-slip motions along shallow fault planes in central Crete (Amourgeles fault). Our results indicate that while crustal extension dominates there is a combination of active fault kinematics, ranging from normal faulting along the northern edge of Messara basin (south-dipping Plakiotissa fault) to strike-slip faulting inside the SE part Heraklion basin (Houdetsi-Tefeli). The combination of active fault motions accommodates a NW-SE extension of the upper crust.